The Relation Between Health and Earnings in Self-Employment - Hessels, Jolanda; Rietveld, Cornelius A.; van der Zwan, Peter (Frontiers in Psychology, 2020)
Multiple studies have shown that, on average, the self-employed are healthier than wage workers. The link between the health of self-employed individuals and their financial performance in terms of earnings is, however, less understood. Based on human capital theory, we expect a positive link between health and earnings among the self-employed. For two reasons, we expect the relationship between health and earnings to be stronger for the self-employed than for wage workers. First, the self-employed can more easily adapt their production activities such that they yield the highest returns to their human capital, including their health. Second, in the short term, the earnings of the self-employed are more dependent on the ability to work than the wages of wage workers. Our empirical analysis draws on data from the Household, Income and Labour Dynamics in Australia (HILDA) survey, a longitudinal dataset (2001-2017). Our outcome variable is an individual’s total income derived from wage work and/or running a business. Health is measured using multi-item constructs for General health, Bodily pain, and Mental health from the Short Form Health Survey (SF-36). We distinguish between wage workers and self-employed individuals with and without employees. Fixed-effects regressions reveal a significant positive relationship between health and earnings. As expected, this relationship is significantly stronger for the self-employed than for wage workers. The latter result holds particularly for the self-employed without employees. We also find that the negative relationship between health and job termination is stronger for the self-employed (without employees) than for wage workers.